2023
DOI: 10.1007/s00590-023-03480-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing recurrent infections after one-stage revision for periprosthetic joint infection of the knee: a systematic review of the literature

Abstract: Background Periprosthetic joint infection (PJI) of the knee represents a severe complication after 1.5% to 2% of primary total knee replacement. Although two-stage revision was considered the gold-standard treatment for PJI of the knee, in the last decades, more studies reported the outcomes of one-stage revisions. This systematic review aims to assess reinfection rate, infection-free survival after reoperation for recurrent infection, and the microorganisms involved in both primary and recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Bone graft: All studies reported data about the prevalence and type of bone graft used in hip revision surgery ( 19 , 25 - 43 ). Bone graft was frequently used in association with TT cups in revision for acetabular bone defects.…”
Section: Resultsmentioning
confidence: 99%
“…Bone graft: All studies reported data about the prevalence and type of bone graft used in hip revision surgery ( 19 , 25 - 43 ). Bone graft was frequently used in association with TT cups in revision for acetabular bone defects.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, analysis of causative microorganisms after reinfection is also necessary. In a systematic review of recurrent infections after 1-stage revision, the causative microorganisms differed significantly from those in the primary infections, with the incidence of gram-positive bacteria found to be 71.1% during the revision surgery but 44.4% during subsequent reinfection 34 . Furthermore, another study on 113 two-stage revision TKAs found that infection recurred in 23 cases.…”
Section: Discussionmentioning
confidence: 98%
“…The Methodological Index for Non-Randomized Studies (MINORS) criteria score ( 35 - 37 ) was used to assess the quality of the included studies. The MINORS criteria score helps assess the relevance of non-randomized surgical research and have been frequently used in the literature regarding systematic reviews on hip and knee studies ( 38 - 40 ).…”
Section: Methodsmentioning
confidence: 99%